Governance of Banjar Song Socialization in Schools - Susyam Widiantho (Universitas Negeri Semarang, 2023)
In the midst of globalization, technology, and the rapidly growing music industry, Banjar songs have started to lose their existence. This can be seen from the fact that many of the current generation, especially those living in urban areas, no longer recognize Banjar songs. Whereas in Lagu Banjar there is local wisdom and socio-cultural values whose presentation has even referred to the concept of Trikon Ki Hadjar Dewantara, but why has Lagu Banjar lost its existence even in the midst of its own